Retirement sorted? The adequacy and optimality of wealth among the near-retired - Rowena Crawford; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2014)
Much of the focus of the UK pensions policy debate over the past decade has been on the adequacy (or otherwise) of private retirement saving. In this paper, we present the first assessment of the optimality of the retirement resources of English couple households born in the 1940s. Here, 'optimal' wealth holdings are those that allow households to enjoy the same level of living standards in both working life and retirement. We use a life-cycle model of consumption and saving to calculate this level of wealth, and compare that with how much wealth households are observed to hold. We find that the majority of households hold more wealth than our model suggests is optimal and that this would still be true even if housing wealth were excluded from observed wealth holdings. A comparison of this approach with the replacement rate approach commonly used to assess the adequacy of households' retirement resources suggests that using a simple replacement rate benchmark could give a misleading picture of households' preparedness for retirement as it cannot capture the vast heterogeneity in households' circumstances.
Keywords: D31; D91; E21; D12; H31; H55; 330; wealth; savings; life-cycle model